Hugh M. Stimson, Fifty-five Tang Poems: A text in the Reading and Understanding of T’ang Poetry. New Haven: Far Eastern Publications, 1976, x, 239 pp. - Maeth Ch., Russell (Estudios de Asia y África, 1979)
-